Ripensando a Clitennestra (Argos, 2025)
Clytemnestra, an adulterous and murderous women, has been seen by the Greeks and transmitted to posterity as a model of feminine infamy and cruelty. During the «strong» years of feminism, Agamnemon's wife was still the object of interesting revisions that looked at her as a model of dignity and courage. Through an exploration of Greek sources, this paper identifies the sources which –by describing the numerous and grave wrongs committed by Agamemnon against his wife (not alluded in Aeschylus' Oresteia)– explain how come Clytemnestra –rather than as a «monstrous» woman– can be regarded as a victim reacting to genre violence in the only way that was possible then. The article also refers lo some interpretations of the Oresteia according to which Orestes' acquittal does not mean -as usually conceived- the defeat of the female and irrational part of the world. To the Erinyes transformed into Eumenides, in fact, Athena would assign a role that might demonstrate that law, to be just, must also give place to emotions.
Keywords: genre violence; Greece; today; reason; emotions; new theories of law